G43(P) Clinical Audit on Advanced Care Plan For Management of Cardio-Respiratory Arrest in Children and Young Person with Advanced Malignancy (Single Centre Experience). (4th June 2013) - Aye, M; Hobin, D
Abstract : Aim: To find out whether children with advanced malignant disease referred to Palliative care team had advanced care plan for management of cardiopulmonary arrest or not. Secondary objectives: To detect designated purple form (Advance care plan-ACP) from the West midland Paediatric palliative care toolkits have been used or not. To identify the heath care profession who involved in making ACP decision. Lastly, to assess place of death related to presence of ACP with DNAR (Do Not Attempt Resuscitation). Methods: Retrospective study of Children with advanced malignant disease who died while under the care of Palliative care team (BCH) during May to October 2011. Data were collected from Palliative care data base, Patients' notes (medical and palliative care notes) and Letters. Standard: Child & Young Person's Advance Care Plan Policy – April 2011West Midlands Paediatric Palliative Care Network, Paediatric Palliative Care toolkit Results: Total number of death from June 2011 to Oct 2011 was 26, 23 with solid Tumour and 3 with haematology malignancy. Age ranged from neonate till 16 years. Eighty percent (21/26) of children had formulated plan for DNAR. Half (51%) used the purple form (ACP from West midland Paediatric Palliative care toolkit), the remaining half either by using other DNAR forms (20%) or letters (28%). Most (90%) of the ACP with DNAR were supported by consultant (paediatric oncologist) and only 10% was by general practitioner. Eighteen children (68%) died at home and all of them had ACP with DNAR. 2 children with ACP with DNAR, died at hospice. 26% (6) died in hospital (oncology ward/PICU), 5 children without ACP and 1 child with ACP in place. All the children (3) with haematological malignancy died in hospital while they were on active treatment without ACP in place. Conclusion: Advanced care plan discussion should start early in the course of illness according to the pace of parents and children at the sensitive manner. The regional standard ACP form (Purple form-Palliative care toolkits) should be used in all cases with life limiting conditions.